The Effect of Job Stress and Job Satisfaction on Organizational Commitment - Lukmanul Hakim; Agi Syarif Hidayat (Indonesian Journal Of Business And Economics, 2018)
The purpose of this study is to determine the effect of job stress and job satisfaction on organizational commitment. The research method used is quantitative research method. Population in this research is employees of marketing department at PT. Toyamilindo Cirebon with 50 people. Sampling technique used is saturated sampling technique, so that all members of the population sampled as many as 50 people. Data retrieval technique uses questionnaire with likert scale as instrument measurement scale. Data analysis techniques used is multiple regression analysis. The results of the research show that: 1) job stress does not have significant effect to organizational commitment, 2) job satisfaction has significant effect to organizational commitment.Keywords : Job stress; job satisfaction; organizational commitment